Development Contextual Based Thematic Teaching Materials to Increase Students 'Learning Interests in Primary School - Mardhatillah, Mardhatillah; Masliana, Ade; Kasmini, Lili; Marlini, Cut; Al Fuad, Zaki; Helminsyah, Helminsyah; Subhananto, Aprian; Musdiani, Musdiani (Jurnal Ilmiah Teunuleh, 2024)
This study aims to describe: 1) To determine the validity of contextual-based thematic teaching materials to increase the learning interest of fourth-grade students of SD Negeri Ujong Tanjong; 2) To evaluate the effectiveness of contextual-based thematic teaching materials to improve the learning interest of fourth-grade students of SD Negeri Ujong Tanjong, and 3) To find out the student's response to contextual-based thematic teaching materials to increase the learning interest of fourth-grade students of SD Negeri Ujong Tanjong. This research is a research development or Research and Development (R&D). This study uses the 4D model (Four D Model). The development stage steps, namely the defining stage (Define), design (Design), development (Develop), and deployment (Disseminate). This research was conducted at SD Negeri Ujong Tanjong, with a total of 20 students. There 18 male students and ten female students. This research aims to contextual-based thematic teaching materials to increase the learning interest of fourth-grade students of SD Negeri Ujong Tanjong. Data collection techniques used were expert validation, questionnaires, interviews, observation, and documentation. The result of this development is a contextual-based thematic teaching material that is suitable for use. The feasibility of teaching materials produced from design expert validation, material expert validation, and linguist validation is ideal for teaching materials. Student responses to teaching materials obtained in field trials were very good, with an average score of 97%.